40Ar/39Ar dating, fluid inclusions and S–Pb isotope systematics of the Shabaosi gold deposit, Heilongjiang Province, China. (6th June 2014) - Liu, Jun; Wu, Guang; Qiu, Huaning; Li, Yuan
<x xml:space="preserve">Abstract</x> The Shabaosi deposit is the only large lode gold deposit in the northern Great Xing'an Range. The gold ore bodies are hosted by sandstone and siltstone of the Middle Jurassic Ershi'erzhan Formation, and are controlled by three N–S‐trending altered fracture zones. The gold ore bodies are composed of auriferous quartz veinlets and altered rocks. Fluid inclusion studies indicate that the ore‐forming fluids belong to a H2O–NaCl–CO2–CH4 system, with salinities between 0.83 and 8.28 wt% NaCl eq., and homogenization temperatures ranging from 180 to 320 °C. The δ34S values of sulphides show a large variation from −16.9‰ to 8.5‰. The Pb isotope compositions of sulphides are characterized by a narrow range of ratios: 18.289 to 18.517 for 206Pb/204Pb, 15.548 to 15.625 for 207Pb/204Pb, and 38.149 to 38.509 for 208Pb/204Pb. The μ values range from 9.36 to 9.51. These results suggest that the ore‐forming fluids/materials were mainly of magmatic hydrothermal origin, derived from magmas produced by partial melting of the lower crust. The 40Ar/39Ar age of auriferous quartz veinlets from the Shabaosi gold deposit is about 130 Ma. The Shabaosi gold deposit has counterparts in similar orogenic gold deposits, and was formed during the post‐collisional setting of the Mongolia–Okhotsk Orogen. Copyright © 2014 John Wiley & Sons, Ltd.